2007
DOI: 10.1007/s00248-006-9192-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Experimental Lead Pollution on the Microbial Communities Associated with Sphagnum fallax (Bryophyta)

Abstract: Ecotoxicological studies usually focus on single microbial species under controlled conditions. As a result, little is known about the responses of different microbial functional groups or individual species to stresses. In an aim to assess the response of complex microbial communities to pollution in their natural habitat, we studied the effect of a simulated lead pollution on the microbial community (bacteria, cyanobacteria, protists, fungi, and micrometazoa) living on Sphagnum fallax. Mosses were grown in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…Their well-defined ecological preferences in relation to important ecological variables in peatlands have made them useful in ecological studies (Charman, 1997). Testate amoebae are excellent indicators of calcite precipitation in lakes (Casper and Scho¨nborn, 1985) and heavy metal pollutants in peatlands (Nguyen-Viet et al, 2007). Previous studies have shown that the abundance of each taxon, and hence the structure of communities, are controlled by a set of environmental variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their well-defined ecological preferences in relation to important ecological variables in peatlands have made them useful in ecological studies (Charman, 1997). Testate amoebae are excellent indicators of calcite precipitation in lakes (Casper and Scho¨nborn, 1985) and heavy metal pollutants in peatlands (Nguyen-Viet et al, 2007). Previous studies have shown that the abundance of each taxon, and hence the structure of communities, are controlled by a set of environmental variables.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, factors such as light, oxygen and food availability may also affect testate amoebae communities (Charman et al, 2000). The ecology of most species is still rather poorly known although there have been a number of recent studies in several regions of the world, including New Zealand (Charman, 2001), north-western Poland (Lamentowicz and Mitchell, 2005), Alaska (Payne et al, 2006), and in France (Nguyen-Viet et al, 2007). Several authors have studied the vertical micro-distribution of testate amoebae in peatlands.…”
Section: Introductionmentioning
confidence: 99%
“…Testate amoebae form a very sensitive group of organisms (Nguyen-Viet et al 2007). Their short generation times make them useful indicators of environmental changes (Vincke et al 2004a, b;Mattheeussen et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The TA community was extracted from the mosses using the method described by Nguyen-Viet et al (2007b) and Meyer et al (2010a,b): each sample was first shaken in a vortex and then filtered through a 180 m mesh filter. Fifteen mL of glutaraldehyde (2% final concentration) were added to the sample.…”
Section: Extractionmentioning
confidence: 99%